Aspect-oriented software for testability - Meetei, Mutum Zico (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
AOP is recently popular for effective technique in modularizing the crosscutting concerns such as exception handling, fault tolerance, error handling and reusability. Modularizing crosscutting concerns has a great impact on testability of software. Testability of software is the degree to facilitate testing in a given test context and ease reveling of faults. Controllability and observability are the important measures of testing non-functional requirements of software. To test software requires controlling the input and observing the output. Controllability provides a concept of probability to handle the software's input (the internal state) while observability is to observe the output for certain input. This paper presents an overview of the use of aspect-oriented programming (AOP) for facilitating controllability to ease testability of object-oriented software, and simulation of well-mixed biochemical systems.